If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -30a = 0 Reorder the terms: -30a + 6x = 0 Solving -30a + 6x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6x' to each side of the equation. -30a + 6x + -6x = 0 + -6x Combine like terms: 6x + -6x = 0 -30a + 0 = 0 + -6x -30a = 0 + -6x Remove the zero: -30a = -6x Divide each side by '-30'. a = 0.2x Simplifying a = 0.2x
| 9+2(v-1)=4(v+1)-5 | | -30x-26.1x+1.5=0 | | -v+3v=4 | | -24x+9.1x-8.2=0 | | 48x-27.4x-28=0 | | 8x-6-4x=-6 | | -7=n+3+4n | | 3bx-4=-bx | | 3x+5-7x=2x-8-x-12 | | M-4m=-6 | | -3x+6.6y=-11.1 | | 2(y-2)+4=31 | | -5x+y=4.4 | | 4(x+y)=4 | | 3x=12-3x | | 7-8(4-x)=3x-5 | | 7+4(2a+15)=-13 | | 8(y+2)=0 | | 5x+4y=16.2 | | 2x+y=22 | | x+3y=11.2 | | -75x-3y=-8.11 | | 8.1x-3.2=7.6x-2.4 | | 5y+3=2(y-1) | | -2x+3y=-61 | | -x+3y=-41 | | -2=7(q+2)+3(2q-1) | | -6+3x=-x-86 | | 2+3y-5=11 | | 6(k+2)+2(2k-5)=22 | | 13=3g-2(-5+g) | | 4a-7=4(a-2)+1 |